Some sample programs written in DryadLINQ - Yu, Yuan; Isard, Michael; Fetterly, Dennis; Budiu, Mihai; Erlingsson, Úlfar; Gunda, Pradeep Kumar; Currey, Jon; McSherry, Frank (2009)
DryadLINQ is a system and a set of language extensions that enable a new programming model for large scale distributed computing. This technical report contains annotated listings of several example programs written using DryadLINQ, illustrating typical usage.